Application of microstructurally-designed mortars for studying early-age properties: Microstructure and mechanical properties. (December 2015) - Di Bella, C.; Wyrzykowski, M.; Griffa, M.; Termkhajornkit, P.; Chanvillard, G.; Stang, H.; Eberhardt, A.; Lura, P.
Abstract: A recently-developed technique for stopping hydration without altering the microstructure by invasive methods is studied. This technique is based on the replacement at the mixing stage of cement/binder grains that would otherwise remain unhydrated in real systems at defined hydration stages with inert quartz particles. This technique allows studying hydration-dependent properties in a static equivalent system, where these processes can be decoupled from hydration. A comprehensive comparison between real and equivalent systems, in terms of mechanical properties as well as physico-chemical ones is presented. Results of mechanical properties support the validity of the approach. Microstructural characterization by means of mercury intrusion porosimetry shows comparable results in terms of total porosity and breakthrough radii. Thermogravimetric analysis shows comparable amounts of hydration products formed. These results suggest that the method can constitute a useful tool for studying the behavior of cementitious materials at early ages, in particular transport phenomena and shrinkage.